Finding new routes for integrating Multi-Agent Systems using Apache Camel - Amaral, Cleber J.; Bernardes, Sérgio P.; Conceição, Mateus; Hübner, Jomi F.; Lampert, Luis P. A.; Matoso, Otávio A.; Zatelli, Maicon R. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2019)
In Multi-Agent Systems (MAS) there are two main models of interaction: among agents, and between agents and the environment. Although there are studies considering these models, there is no practical tool to afford the interaction with external entities with both models. This paper presents a proposal for such a tool based on the Apache Camel framework by designing two new components, namely camel-jason and camel-artifact. By means of these components, an external entity is modelled according to its nature, i.e., whether it is autonomous or non-autonomous, interacting with the MAS respectively as an agent or an artifact. It models coherently external entities whereas Camel provides interoperability with several communication protocols.